STUDI PENGEMBANGAN NANOFLUIDA HIJAU BERASAL DARI BAHAN LOKAL ALAM UNTUK APLIKASI DI BIDANG TEKNIK - Kushendarsyah Saptaji; Alvika Meta Sari; Anwar Ilmar Ramadhan; Istianto Budhi Rahardja; Muhammad Dadi Saputra; Firmansyah Firmansyah; Efrizon Umar (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
The increase in energy demand causes a continuous increase in global temperatures exceeding pre-industrial temperatures with the release of toxic gases and radiation causing severe climate conditions. So, it is mandatory to develop durable and highly efficient thermal systems to overcome these problems. There has been much research into nanofluids to improve performance in thermal applications and have gained significant attention over the past few years due to their superior qualities. Additionally, other undesirable effects such as corrosion of equipment, non-biodegradable by-products occur due to the presence of strong chemicals. Therefore, the development of cost-effective and environmentally friendly nanofluids has emerged as a fast-growing alternative research field with many enthusiasts. The current review provides a comprehensive view of the various techniques used in the preparation of green nanofluids using several natural extracts. The unique morphology, optical properties, stability, high surface area, lower toxicity, and improved thermo-physical properties of green nanoparticles make them favorable choice candidates in enhancing the performance of thermal systems.